Highly sensitive rapid test with chemiluminescent signal bands - Kim, Hyung-Seok; Ko, Hyuk; Kang, Min-Jung; Pyun, Jae-Chul (KOREAN BIOCHIP SOCIETY-KBCS, 2010)
The lateral flow immunoassay called "rapid test" has been widely used for medical diagnosis, environmental monitoring, forensic tests, and so on. This method carries out whole immunoassay process including washing and signal reporting simply by dropping a sample to a test strip. During the capillary flow of a sample on the test strip, colored signal bands are produced by the targeted antigen-antibody interactions. In this study, a highly sensitive rapid test was developed by applying a chemiluminescence enzyme reaction. In this method, a chemiluminescent signal band was produced by using horseradish peroxidase (HRP) labeled antibodies and luminol as a chemiluminescence substrate. The intensity of the chemiluminescent signal band was evaluated by using a charge coupled device (CCD) with an image analysis program. The feasibility of the new rapid test with a chemiluminescent signal band was presented by the detection of horseradish peroxidase (HRP) as a model analyte. The applicability of this new rapid test to sandwich-type immunoassays was demonstrated by the detection of myoglobin, and the sensitivity was determined to be improved as much as 100-fold in compared to the conventional rapid test based on colored gold-colloids.
Keywords: LATERAL-FLOW IMMUNOASSAY; MYOCARDIAL-INFARCTION; EARLY-DIAGNOSIS; MYOGLOBIN; PROTEIN; ISOFORMS; FORMAT; ASSAY